The implications of Brexit for the electricity sector in Great Britain: Trade-offs between market integration and policy influence. (November 2017) - Lockwood, Matthew; Froggatt, Antony; Wright, Georgina; Dutton, Joseph
Abstract: This paper examines the trade-off between the economic gains to Great Britain (GB) from being integrated into the EU electricity market on the one hand and a loss of influence over policy and rule making on the other. The aim is not to predict how this trade-off will be resolved in practice, but rather to lay out what is at stake on both sides of the equation. Since the late 2000s the electricity market in GB has become increasingly integrated with continental European markets through market coupling and increasing interconnection capacity, with further integration expected up to the mid-2020s. Estimates of the economic benefits of this integration range up to the order of several £100 m to £1bn a year, representing the economic cost of a reversal of such integration. On the other hand, maintaining and expanding electricity market integration would require the acceptance of electricity policies and regulations made in European institutions in which UK actors would have little if any voice. An intermediate multilateral approach offering the possibility of retaining market integration with less cost in terms of influence is proposed. Highlights: Outlines economic benefits and sovereignty costs of EU electricity integration. Considers trade-offs in 'hard' and 'soft' electricity Brexit scenarios. Proposes alternative intermediate multilateral approach.